A Comparative ınvestigation of sub-components of the environmental literacy at the secondary school level - Sontay, Gökhan; Gökdere, Murat; Usta, Erdoğan (Journal of Turkish Science Education, 2015)
The purpose of this research is to determine the correlation between “environmental knowledge”, “environmental effect” and “environmental behavior” which are accepted as environmental literacy components. “Environmental Knowledge Test (EKT), “Environmental Affect Scale (EAS)” and “Environmental Behavior Scale (EBS), which have been prepared by the researchers and their validity and reliability ensured, have been used as the measurement tools. The research group is composed of 364 students from 6 different secondary schools in the center of Amasya city providing education in the school year of 2011-2012. Correlational research method was used in the study. The Pearson Correlation Test has been used for analysis of the data. As a result of the research; it was found that there was a positive and high correlation at 0,858 strength between the “environmental knowledge” component and “environmental affect” component; a positive and low correlation at 0,426 strength between the “environmental knowledge” component and “environmental behavior” component; a positive medium level correlation at 0,502 strength between the “environmental affect” variable and “environmental behavior” variable. The results obtained from the investigation are of great importance in terms of shedding light on the issue for determination of how environmental literacy components affect each other.